Catalyst for oxidative dehydrogenation and preparation method thereof
By preparing spinel metal oxide nanoparticles and fixing them on the support, the problem of side reaction of existing catalysts during butene oxidation and dehydrogenation is solved, the reactivity and selectivity of the catalyst are improved, and efficient Butene conversion and 1,3-butadiene production.
Patent Information
- Application Number
- CN202111159518.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-06-07
- Filing Date
- 2017-05-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2037-05-18
AI Technical Summary
The existing metal oxide catalysts have side reaction problems in the oxidation and dehydrogenation process of butene, resulting in an increase in the amount of catalyst and low reaction efficiency, and a small uniformity and surface area of the catalyst.
Metal oxide nanoparticles with spinel structure were prepared and fixed on a support to form a catalyst with high butene conversion and excellent side reaction inhibition effect.
By increasing the surface area of the catalyst, the reactivity and product selectivity are improved, and the generation of side reactions is reduced, thereby achieving efficient butene conversion and 1,3-butadiene production.
Smart Images

Figure CN113877584B_ABST
Abstract
Description
[0001] This application is a divisional application. The international application number of the original application is PCT / KR2017 / 005162, the international application date is May 18, 2017, the Chinese national application number is 201780003408.6, the entry date into the Chinese national phase is March 30, 2018, and the name of the invention is “Catalyst for oxidative dehydrogenation and preparation method thereof”. Technical Field
[0002] [CROSS-REFERENCE TO RELATED APPLICATIONS]
[0003] This application claims the benefit of priority from Korean Patent Application No. 10-2016-0070102 filed on June 7, 2016 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference.
[0004] The present invention relates to a catalyst for oxidative dehydrogenation and a method for preparing the same. More specifically, the present invention relates to a catalyst for oxidative dehydrogenation of butene and a method for preparing the same, wherein the catalyst has a high butene conversion rate and an excellent side reaction inhibition effect by preparing metal oxide nanoparticles and then fixing the prepared metal oxide nanoparticles on a carrier, thereby having high reactivity and high selectivity to products. Background Art
[0005] Globally, the demand for 1,3-butadiene, an intermediate of petrochemical products, and its value are gradually increasing. In order to produce this 1,3-butadiene, methods such as naphtha cracking, direct butene dehydrogenation and oxidative dehydrogenation of butene have been used. However, in the case of naphtha cracking, due to the high reaction temperature, the energy loss is high. In addition, since naphtha cracking is not a process specifically designed for the production of 1,3-butadiene products, other base oils other than 1,3-butadiene are unfavorably generated as excess products. At the same time, the direct dehydrogenation of n-butene is thermodynamically unfavorable. In addition, since the direct dehydrogenation of n-butene is an endothermic reaction, high temperature and low pressure conditions are required to produce 1,3-butadiene in high yield. Therefore, the direct dehydrogenation of n-butene is not suitable as an industrial method for producing 1,3-butadiene.
[0006] Meanwhile, in the case of oxidative dehydrogenation of butene, since butene reacts with oxygen to generate 1,3-butadiene and water in the presence of a metal oxide catalyst to generate stable water, the oxidative dehydrogenation of butene is thermodynamically favorable. In addition, since the oxidative dehydrogenation of butene is an exothermic reaction, unlike the direct dehydrogenation of butene, the oxidative dehydrogenation of butene can produce 1,3-butadiene in high yield even at a low reaction temperature compared to the direct dehydrogenation of butene. In addition, since the oxidative dehydrogenation of butene does not require additional heat supply, the oxidative dehydrogenation of butene can be considered as an effective production method for producing only 1,3-butadiene, thereby meeting the demand for 1,3-butadiene.
[0007] Such metal oxide catalysts are usually synthesized by a coprecipitation method in which a metal solution is simultaneously precipitated with an alkaline solution. However, in the mass production of metal oxide catalysts prepared by the coprecipitation method, the uniformity is poor due to the different precipitation conditions of the individual metal cations therein, and the surface area per unit volume is small due to its size of several microns. This problem promotes side reactions during the oxidative dehydrogenation process and increases the amount of catalyst used.
[0008] Therefore, there is an urgent need to develop a catalyst that can be used in a reduced amount by suppressing side reactions and has improved catalytic activity.
[0009] [Related technical literature]
[0010] [Patent Document] (Patent Document 1) KR0888143 B1 Summary of the invention
[0011] Technical issues
[0012] Therefore, the present invention is made in view of the above problems. One object of the present invention is to provide a catalyst for the oxidative dehydrogenation of butene, which is prepared by preparing metal oxide nanoparticles having a spinel structure and then fixing the prepared metal oxide nanoparticles on a carrier. The catalyst has a high butene conversion rate and an excellent side reaction inhibition effect, thereby having high reactivity and high selectivity for the product.
[0013] The above-mentioned objects and other objects can be achieved by the present disclosure described below.
[0014] Technical Solution
[0015] According to one aspect of the present invention, there is provided a catalyst for oxidative dehydrogenation, comprising: a metal oxide having a composition represented by the following Formula 1 and having an average particle size of 0.1 nm to 50 nm; and a carrier:
[0016] [Formula 1]
[0017] AB2O4
[0018] wherein A is, for example, one or more selected from divalent cationic metals, and B is, for example, one or more selected from trivalent cationic metals.
[0019] According to another aspect of the present invention, a method for preparing a catalyst for oxidative dehydrogenation is provided, wherein the preparation method is carried out by loading or coating a nanoscale metal oxide on a carrier, and comprises the following steps: obtaining a mixed solution by mixing a precursor of a divalent cationic metal (A), a precursor of a trivalent cationic metal (B), an organic solvent, an unsaturated fatty acid and a surfactant, and then heating the mixed solution at 100° C. to 350° C. to prepare a metal oxide having a composition represented by the following Formula 1 and an average particle size of 0.1 nm to 50 nm.
[0020] Beneficial Effects
[0021] As is apparent from the above description, the present invention advantageously provides a catalyst for oxidative dehydrogenation having excellent side reaction suppression effect, excellent reactivity and excellent selectivity to products due to the inclusion of metal oxide nanoparticles, and a method for efficiently preparing the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 shows a schematic diagram of a preferred embodiment according to the present invention;
[0023] Figure 2 A transmission electron microscope (TEM) photograph of metal oxide nanoparticles prepared according to the present invention is shown;
[0024] Figure 3 shows the X-ray diffraction results of metal oxide nanoparticles prepared according to the present invention;
[0025] Figure 4 The X-ray diffraction results of the catalysts prepared according to the present invention and conventional techniques are shown. DETAILED DESCRIPTION
[0026] Hereinafter, the present invention is described in detail.
[0027] The present inventors have confirmed that when a metal oxide is prepared using nanoparticles and the prepared metal oxide is coated or loaded on a carrier to prepare a catalyst, the surface area per unit volume of the catalyst increases during oxidative dehydrogenation, thereby exhibiting excellent reactivity and excellent selectivity to products, thereby completing the present invention.
[0028] Oxidative dehydrogenation refers to a reaction of generating a conjugated diene and water by a reaction between an olefin and oxygen in the presence of a metal oxide. In particular, oxidative dehydrogenation may be a reaction of generating 1,3-butadiene and water by a reaction between butene and oxygen.
[0029] The reactor for oxidative dehydrogenation is not particularly limited as long as it is suitable for oxidative dehydrogenation. For example, the reactor may be a reactor in which the reaction temperature of the catalyst layer loaded is kept constant, and oxidative dehydrogenation is carried out as the reactants continuously pass through the catalyst layer. As a specific example, the reactor may be a tubular reactor, a batch reactor, a fluidized bed reactor or a fixed bed reactor. Here, the fixed bed reactor may be, for example, a multi-tubular reactor or a plate type reactor.
[0030] The reactant of oxidative dehydrogenation can be, for example, one or more selected from butane, isobutane, 1-butene, trans-2-butene and cis-2-butene and oxygen. In addition, the reactant can also contain nitrogen and water vapor.
[0031] Now, the catalyst for oxidative dehydrogenation according to the present invention is described in detail.
[0032] The catalyst for oxidative dehydrogenation is characterized by comprising: a metal oxide having a composition represented by the following Formula 1 and an average particle size of 0.1 nm to 50 nm; and a carrier:
[0033] [Formula 1]
[0034] AB2O4
[0035] wherein A is, for example, one or more selected from divalent cationic metals, in particular one or more selected from Cu, Ra, Ba, Sr, Ca, Cu, Be, Fe(II), Zn, Mg, Mn, Co and Ni, preferably one or more selected from Zn, Mg, Mn, Co and Ni.
[0036] B is, for example, one or more selected from trivalent cationic metals, specifically one or more selected from Al, Fe(III), Cr, Si, V, Ga, In, La and Ce, preferably one or more selected from Al, Fe(III) and Cr.
[0037] The metal oxide having a composition represented by Formula 1 may be, for example, a metal oxide having a spinel structure. The spinel structure may be understood as a structure in which a unit lattice of a cubic system is composed of 8 divalent cations, 16 trivalent cations, and 32 oxygen ions, the oxygen ions mainly forming a face-centered cubic lattice, and the divalent cations (A) and the trivalent cations (B) fill the space between the oxygen ions.
[0038] The average particle size of the metal oxide may be, for example, 0.1 nm to 50 nm, or 1 nm to 30 nm. Within the range, the surface area per unit volume thereof is large, thereby providing excellent reactivity and excellent selectivity to products in the oxidative dehydrogenation process.
[0039] The loading or coating amount of the metal oxide may be, for example, 1 to 40 parts by weight, 5 to 30 parts by weight, or 5 to 20 parts by weight based on 100 parts by weight of the carrier contained in the catalyst for oxidative dehydrogenation. Within the range, effective dispersion of the nanoparticles may be provided.
[0040] The support is not particularly limited as long as the metal oxide can be supported or coated thereon. For example, the support may include one or more selected from alumina, silica, cordierite, titania, zirconia, silicon nitride, and silicon carbide.
[0041] Figure 1 Schematic diagram showing the shape of the catalyst for oxidative dehydrogenation according to the present invention. Figure 1 , the catalyst for oxidative dehydrogenation may have a form in which, for example, nano-scale metal oxides are uniformly distributed and supported or coated on a carrier.
[0042] The catalyst for oxidative dehydrogenation may be, for example, a supported catalyst.
[0043] The average particle size of the catalyst for oxidative dehydrogenation according to the present invention is, for example, 0.1 nm to 50 nm, and thus the surface area per unit volume is increased compared to a bulky catalyst. Therefore, within the range, the activity of the catalyst is improved, and an excellent side reaction suppression effect is exhibited, thereby exhibiting excellent reactivity and excellent selectivity to the product.
[0044] The preparation method of the catalyst for oxidative dehydrogenation according to the present invention is carried out by loading or coating a nanometer-sized metal oxide on a carrier, and comprises the following steps: obtaining a mixed solution by mixing a precursor of a divalent cationic metal (A), a precursor of a trivalent cationic metal (B), an organic solvent, an unsaturated fatty acid and a surfactant, and then heating the mixed solution at 100° C. to 350° C. to prepare a metal oxide having a composition represented by the following Formula 1 and an average particle size of 0.1 nm to 50 nm:
[0045] [Formula 1]
[0046] AB2O4
[0047] wherein A is, for example, one or more selected from divalent cationic metals, in particular one or more selected from Cu, Ra, Ba, Sr, Ca, Cu, Be, Fe(II), Zn, Mg, Mn, Co and Ni, preferably one or more selected from Zn, Mg, Mn, Co and Ni.
[0048] B is, for example, one or more selected from trivalent cationic metals, specifically one or more selected from Al, Fe(III), Cr, Si, V, Ga, In, La and Ce, preferably one or more selected from Al, Fe(III) and Cr.
[0049] The precursor of the divalent cationic metal (A) may be selected from, for example, zinc acetate, zinc acetylacetonate, magnesium acetate, magnesium acetylacetonate, manganese acetate, manganese acetylacetonate, cobalt acetate, cobalt acetylacetonate, nickel acetate, and nickel acetylacetonate.
[0050] The precursor of the trivalent cationic metal (B) may be selected from, for example, aluminum acetate, aluminum acetylacetonate, iron acetate, iron acetylacetonate, chromium acetate, and chromium acetylacetonate.
[0051] For reference, in the present invention, it is not suitable to use a chloride-based precursor as a metal precursor because it requires an additional process to generate a metal-oleate intermediate.
[0052] The precursor of the divalent cationic metal (A) and the precursor of the trivalent cationic metal (B) may be dissolved in the organic solvent, for example, at a molar ratio (B / A) of 1.5 to 10, 1.5 to 5, or 2 to 3. Within the range, single-phase metal oxide nanoparticles may be obtained.
[0053] The boiling point of the organic solvent may be, for example, 250° C. or more. In a specific example, as the organic solvent, hexadecane, hexadecene, octadecane, octadecene, phenanthrene, diphenyl ether, octyl ether, dibenzyl ether, etc. may be used alone, or a mixture of two or more thereof may be used. For reference, when an organic solvent having a boiling point of less than 250° C. is used, the generation and growth of metal oxide nanoparticles are insufficient, and thus, the particles are insufficiently generated.
[0054] Unsaturated fatty acids and surfactants control the entanglement of metal oxide nanoparticles in the process of pyrolysis in organic solvents. Therefore, the average particle size of metal oxide nanoparticles can be regulated by controlling the ratio of unsaturated fatty acids and surfactants added in the organic solvent. Preferably, in view of the dispersion of precursor, unsaturated fatty acids and surfactants are pre-mixed in the organic solvent to be used. Here, based on 100 weight parts of organic solvents, the total content of unsaturated fatty acids and surfactants can be 1 weight part to 60 weight parts, or 3 weight parts to 60 weight parts.
[0055] As a specific example, the content of the unsaturated fatty acid may be 3 parts by weight to 30 parts by weight, and the content of the surfactant may be 3 parts by weight to 30 parts by weight, based on 100 parts by weight of the organic solvent.
[0056] For example, as the unsaturated fatty acid, lauric acid, palmitic acid, oleic acid, stearic acid, etc. may be used alone, or a mixture of two or more thereof may be used.
[0057] For example, as the surfactant, octylamine, trioctylamine, decylamine, dodecylamine, tetradecylamine, hexadecylamine, oleylamine, octadecylamine, tribenzylamine, triphenylamine, etc. may be used alone, or a mixture of two or more thereof may be used.
[0058] Regarding the use of unsaturated fatty acids and surfactants, oleic acid and oleamide can be used in various combinations based on the following application examples. For example, oleic acid and oleamide can be included in a molar ratio of 1:1 to 10:1, 1:1 to 5:1 or 1:1 to 2:1. Within the range, the average particle size can be effectively adjusted while preventing the metal oxide nanoparticles from entangled. For reference, when the molar ratio exceeds the upper limit, the sample usage is larger than the required amount, thereby reducing the particle size adjustment and being uneconomical. When the molar ratio is less than the lower limit, the particles aggregate, thereby, particles of uniform size cannot be provided.
[0059] Subsequently, the mixed solution is heated to 100°C to 350°C to prepare a metal oxide having a composition represented by Formula 1 below and an average particle size of 0.1nm to 50nm. The heating is preferably performed in a multi-stage manner to prepare particles having uniform size and composition. For example, the heating may be performed in the following manner: the temperature is increased to 100°C or more or 100°C to 120°C at a heating rate of 1°C / min to 10°C / min, and the increased temperature is maintained for 30 minutes to 1 hour, followed by increasing the temperature to 190°C or more or 190°C to 210°C at a heating rate of 1°C / min to 10°C / min, and the increased temperature is maintained for 1 hour to 2 hours.
[0060] Subsequently, the solution is heated to 290° C. or higher or 290° C. to 310° C. at a temperature increase rate of 1° C. / min to 5° C. / min, and then refluxed for 1 to 2 hours.
[0061] The step of loading and coating the metal oxide nanoparticles on a carrier to provide the catalyst for oxidative dehydrogenation of the present invention is intended to uniformly spray the particles onto the structure, and may be appropriately changed based on the conditions used in the art.
[0062] For example, after the step of loading or coating the metal oxide nanoparticles on the carrier, a step of drying the loaded or coated carrier may be included. After the drying step, a firing step may be included as needed.
[0063] In another embodiment, the metal oxide nanoparticles may be dispersed in a solvent having a boiling point of 69° C. or less (e.g., hexane or methylpentane), and then supported on a carrier, followed by slow drying at a temperature lower than the boiling point of the solvent used. Thus, the metal oxide nanoparticles may be satisfactorily fixed to the carrier while being uniformly dispersed on the carrier, whereby the catalytic reaction may be effectively performed without desorption of the metal oxide nanoparticles in the subsequent oxidative dehydrogenation process.
[0064] For example, drying may be performed at room temperature to 62°C, or at 40°C to 60°C.
[0065] Now, the present invention will be described in more detail with reference to the following preferred embodiments. However, these embodiments are provided for illustrative purposes only. It will be appreciated by those skilled in the art that various modifications, additions and substitutions may be made without departing from the scope and spirit of the present invention. Therefore, it is apparent that these modifications, additions and substitutions are within the scope of the present invention.
[0066] [Example]
[0067] Example 1
[0068] 20 ml of octyl ether as an organic solvent, 4 mmol of oleic acid as an unsaturated fatty acid, and 4 mmol of oleylamide as a surfactant were added to the flask, followed by mixing.
[0069] 2.507 g of powdered zinc acetylacetonate (Zn(C5H7O2)3) as a precursor of a divalent cationic metal (A) and 3.053 g of powdered iron acetylacetonate (Fe(C5H7O2)3) as a precursor of a trivalent cationic metal (B) were added to the mixed solution (molar ratio of Zn:Fe=1:2) and reacted at 110°C for one hour to remove excess water and oxygen.
[0070] Then, the temperature was raised to 200°C and maintained for two hours. Then, the temperature was raised to 300°C and maintained for one hour, and then cooled. Then, the recovery process was performed.
[0071] Transmission electron microscopy (TEM) images of the prepared metal oxide nanoparticles are shown in Figure 2 In. Reference Figure 2The XRD analysis results of the prepared metal oxide nanoparticles are shown in Figure 3 In. Reference Figure 3 , it can be confirmed that the metal oxide nanoparticles have the spinel structure of ZnFe2O4.
[0072] The metal oxide nanoparticles were dispersed in hexane and then loaded onto a silica support (Silica Gel 60, Merck) by impregnation, followed by drying at 60° C. Here, 10 parts by weight of the metal oxide nanoparticles were loaded onto 100 parts by weight of the support.
[0073] The X-ray diffraction analysis pattern of the prepared catalyst is shown in Figure 4 It can be confirmed that after loading, the nanoparticles having a spinel structure are distributed on the carrier. In addition, it can be confirmed by X-ray diffraction analysis that the particle size of the nanoparticles is 17nm (see Table 1).
[0074] Example 2
[0075] A catalyst was prepared in the same manner as in Example 1, except that oleic acid and oleamide were used in an amount of 6 mmol, respectively.
[0076] Example 3
[0077] A catalyst was prepared in the same manner as in Example 1, except that oleic acid and oleamide were used in an amount of 8 mmol, respectively.
[0078] Comparative Example 1
[0079] ZnFe2O4 as a commercial spinel oxide and a silica carrier (silica gel, 60, Merck) were sintered separately at 600°C. Subsequently, 10 parts by weight of ZnFe2O4 were mixed with 100 parts by weight of the silica carrier, and the resulting mixture was used in the experiment. The X-ray diffraction analysis pattern of the prepared catalyst is shown in Figure 4 X-ray diffraction analysis confirmed that the average particle size of the obtained nanoparticles was 90 nm (see Table 1).
[0080] Comparative Example 2
[0081] 200 g of distilled water was added to a flask, and 0.28 g of zinc chloride (ZnCl2) and 1.13 g of ferric chloride (FeCl3) were added thereto, followed by mixing to prepare a mixture. The mixture was impregnated with the same support as used in Example 1.
[0082] The impregnated solution was dried at 90°C and then fired at 600°C to prepare a catalyst. Here, 10 parts by weight of the metal oxide was loaded on 100 parts by weight of the carrier. The X-ray diffraction analysis pattern of the prepared catalyst is shown in Figure 4 In the case of Comparative Example 2, the particles were uniformly distributed on the surface of the structure, and therefore, the diffraction size could not be measured.
[0083] The metal oxides prepared according to Examples 1 to 3 and Comparative Example 1, respectively, are summarized in Table 1 below.
[0084] [Table 1]
[0085] category Particle size (nm) Example 1 17 Example 2 14 Example 3 10 Comparative Example 1 90
[0086] [Experimental example]
[0087] Butadiene was prepared by the following method using the catalysts for oxidative dehydrogenation prepared according to Example 1 and Comparative Examples 1 and 2, respectively. The results are summarized in Table 2 below.
[0088] Butadiene preparation
[0089] A mixture of trans-2-butene and cis-2-butene and oxygen is used as a reactant, and nitrogen and water vapor are additionally introduced thereto. As a reaction composition, the volume ratio of oxygen to nitrogen to water vapor is 1:4:5. Butene is composed of trans-2-butene and cis-2-butene mixed in a volume ratio of 60% to 40%. The reaction is carried out under the conditions of a gas hourly space velocity (GHSV) of 125 based on butene and a reaction temperature of 400°C. A metal tube fixed bed reactor is used as a reactor. A metal tube fixed bed reactor is filled with 2cc of a catalyst prepared according to each embodiment and comparative example, and water vapor is injected therein. Regarding water vapor injection, water is vaporized to water vapor at 120°C using a vaporizer, and water vapor is mixed with a butene mixture and oxygen as a reactant, and then introduced into the reactor together. After the reaction, the product is analyzed by gas chromatography (GC). Based on the measurement results of gas chromatography, butene conversion, butadiene selectivity, COx selectivity and yield were calculated according to the following mathematical formulas 1 to 4, respectively:
[0090] [Mathematical formula 1]
[0091] Conversion rate (%) = (number of moles of butene reacted / number of moles of butene added) × 100
[0092] [Mathematical formula 2]
[0093] Butadiene selectivity (%) = (the number of moles of 1,3-butadiene produced / the number of moles of butene reacted) × 100
[0094] [Mathematical formula 3]
[0095] COx selectivity (%) = [(the number of moles of CO2 generated + the number of moles of CO / the number of moles of butene reacted) / 4] × 100
[0096] [Formula 4]
[0097] Yield (%) = (number of moles of 1,3-butadiene produced / number of moles of butene added) × 100
[0098] [Table 2]
[0099]
[0100] As shown in Table 2, it can be confirmed that in the case of Example 1 prepared according to the present invention, a high butene conversion rate and a high butadiene selectivity are exhibited. It can be confirmed that in the case of Comparative Example 2 prepared according to a conventional method, a large amount of COx as a by-product is generated in the supported catalyst. In addition, it can be confirmed that the catalyst according to Comparative Example 1 using commercially available ZnFe2O4 as a metal oxide has a large particle size, whereby both the butene conversion rate and the butadiene yield are reduced.
[0101] In summary, it can be confirmed that when metal oxides are used as nanoparticles and a catalyst prepared by coating or loading the metal oxides on a carrier to prepare a catalyst for oxidative dehydrogenation is used for oxidative dehydrogenation, since the catalyst has a large surface area per unit volume, a catalyst having excellent reactant conversion, capable of suppressing the generation of COx as a by-product, and having excellent selectivity for butadiene as a product can be obtained.
Claims
1. Use of a catalyst in oxidative dehydrogenation, wherein: The catalyst is prepared by the following method, wherein the preparation method is carried out by loading or coating a nano-scale metal oxide onto a carrier, wherein the carrier comprises one or more selected from alumina, silica, cordierite, titania, zirconia and silicon carbide, and The preparation method comprises the following steps: A mixed solution is obtained by mixing a non-chloride precursor of Zn, a non-chloride precursor of Fe(III), an organic solvent, an unsaturated fatty acid and a surfactant, The mixed solution is then heated to 100° C. to 120° C. at a heating rate of 1° C. to 10° C. / min, and the raised temperature is maintained for 30 minutes to 1 hour. Subsequently, the temperature is raised to 190° C. to 210° C. at a heating rate of 1° C. to 10° C. / min, and the raised temperature is maintained for 1 hour to 2 hours. Subsequently, the mixed solution is heated to 290° C. to 310° C. at a heating rate of 1° C. to 5° C. / min, and then refluxed for 1 hour to 2 hours to prepare a metal oxide having a composition represented by the following Formula 1 and an average particle size of 1 nm to 30 nm: [Formula 1] ZnFe2O4, The metal oxide nanoparticles are then dispersed in hexane, and It is then loaded onto a carrier and subsequently dried at a temperature below the boiling point of hexane. Wherein, based on 100 parts by weight of the support, the content of the metal oxide is 5 parts by weight to 20 parts by weight, and the metal oxide has a spinel structure, Wherein, based on 100 parts by weight of the organic solvent, the content of the unsaturated fatty acid is 3 parts by weight to 30 parts by weight, and the content of the surfactant is 3 parts by weight to 30 parts by weight, The organic solvent is one or more selected from hexadecane, hexadecene, octadecane, octadecene and octyl ether, The unsaturated fatty acid is one or more selected from lauric acid, palmitic acid, oleic acid and stearic acid, and The surfactant is one or more selected from octylamine, trioctylamine, decylamine, dodecylamine, tetradecylamine, hexadecylamine, oleamide, octadecylamine, tribenzylamine and triphenylamine.
2. The use according to claim 1, wherein The non-chloride precursor of Zn and the non-chloride precursor of Fe(III) are mixed in a molar ratio of 1.5 to 3.
3. The use according to claim 1, wherein: The molar ratio of the unsaturated fatty acid to the surfactant is 1:1 to 10:1.
